Experimental Investigation on the Acoustic Insulation Properties of Filled Paper Honeycomb-Core Wallboards - Yiheng Song; Haixia Yang; Nanxing Zhu; Jinxiang Chen (Biomimetics)
Honeycomb plates, due to their multi-cavity structure, exhibit excellent mechanical properties and sound insulation. Previous studies have demonstrated that altering the cell size and arrangement of honeycomb structures impacts their acoustic performance. Based on these findings, this study developed a wallboard structure with enhanced sound insulation by filling the cavities with paper fiber/cement facesheets and designing a stacked core structure. Through the reverberation chamber–anechoic chamber sound insulation experiment under 100–6300 Hz excitation and conducting orthogonal experiments from three dimensions, it was found that: (1) Compared to no filling, the filling with straw and glazed hollow bead can increase the sound transmission loss (STL) by more than 50% in the frequency bandwidth above 2000 Hz. This indicates that both types of fillings can significantly enhance the sound insulation performance of the honeycomb structure without a significant increase in economic costs. (2) The increase in paper fiber/cement facesheets improves the STL across the entire experimental bandwidth, with a maximum improvement exceeding 70%. This structural design not only offers superior sound insulation performance but also better suits practical engineering applications. (3) Increasing the number of core stacking units (from one to three), taking straw-filled paper honeycomb-core wallboards as an example, effectively increased the STL bandwidth. (4) This test enriches the application of honeycomb plates in sound insulation. Introducing fiber paper fiber/cement facesheets and eco-friendly, low-cost straw improves sound insulation and enhances the strength of honeycomb, making them more suitable for construction, particularly as non-load-bearing structures.